2017
DOI: 10.1007/s10899-017-9704-4
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Internet-Based Treatment for Problem Gamblers and Concerned Significant Others: A Pilot Randomized Controlled Trial

Abstract: Problem gambling creates significant harm for the gambler and for concerned significant others (CSOs). While several studies have investigated the effects of individual cognitive behavioral therapy (CBT) for problem gambling, less is known about the effects of involving CSOs in treatment. Behavioral couples therapy (BCT) has shown promising results when working with substance use disorders by involving both the user and a CSO. This pilot study investigated BCT for problem gambling, as well as the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 66 publications
4
40
1
1
Order By: Relevance
“…For CSOs, the differences in outcomes were surprisingly small, considering that the CBT condition for CSOs was a control group. This differs from the results of the pilot trial, as well as other trials offering support to CSOs …”
Section: Discussioncontrasting
confidence: 91%
“…For CSOs, the differences in outcomes were surprisingly small, considering that the CBT condition for CSOs was a control group. This differs from the results of the pilot trial, as well as other trials offering support to CSOs …”
Section: Discussioncontrasting
confidence: 91%
“…It is reasonable to assume that many partners have shared finances, which increases their insight into each other’s financial situation (Gunnarsson and Wahlund 1997; Heimdal and Houseknecht 2003). Moreover, the qualitative assessment conducted as part of the pilot testing of the intervention evaluated in the RCT revealed that some gamblers, especially in parent–child dyads, appear to have been pressured into participation by their CSO (Nilsson et al 2018). This could affect the gambler’s willingness to reveal details about his or her gambling.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments were based on cognitive behavioral therapy, and they were internet-based, with therapist support being provided via email and telephone (c.f., Carlbring and Smit 2008). Data are also included from a pilot study (Nilsson et al 2018) conducted prior to the randomized controlled trial (RCT). The pilot and the RCT data were pooled, since the recruitment and screening processes were identical, and recruitment into the RCT followed immediately after the completion of the pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Les résultats encourageants ont montré des tailles 6 d'effets importantes en fin de traitement avec un maintien à 6, 18 et 36 mois. Depuis, quelques études ont pu confirmer l'efficacité de la TCC à distance [16][17][18]. En 2016, Luquiens et al [19] ont utilisé les données de comptes de joueurs de poker pour évaluer l'efficacité de trois modalités de psychothérapie à distance (retour personnalisé [ou feedback], TCC personnalisée avec thérapeute, TCC sans thérapeute).…”
Section: Big Data Et Médecine Préventiveunclassified